2018
DOI: 10.1002/nau.23465
|View full text |Cite
|
Sign up to set email alerts
|

Three month clinical results with a rechargeable sacral neuromodulation system for the treatment of overactive bladder

Abstract: Aims: The primary aim of the RELAX-OAB study is to confirm the safety and efficacy of the Axonics r-SNM System, a miniaturized, rechargeable SNM system. Methods: A total of 51 OAB patients were implanted in a single-stage implant procedure. These results represent the 3-month outcomes. Subject outcomes were evaluated using 3-day bladder diaries and quality of life questionnaires. Results: A total of 31 of 34 patients (91%) that responded during an initial trial period ("Test Responders") continued to benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…As previously reported, 34 of 51 (71%) subjects were Test Responders at the end of the 1‐month trial period, including 28 subjects with UI and 33 subjects with UF.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…As previously reported, 34 of 51 (71%) subjects were Test Responders at the end of the 1‐month trial period, including 28 subjects with UI and 33 subjects with UF.…”
Section: Resultssupporting
confidence: 66%
“…Implanted subjects included 51% previously treated with other 3rd line OAB therapy including percutaneous tibial nerve stimulation and/or Onabotulinum toxinA intradetrusor (Botox) injections. Detailed baseline characteristics were previously published …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A key aspect to realizing the cost benefit of rechargeable SNM therapy is the compliance of subjects with recharging their systems. The 3-month safety and efficacy results 7 and high rates of therapy satisfaction in this report suggest that, in the short-term, subjects are not burdened by and are compliant with recharging their system. Long-term follow-up is necessary to confirm the benefits of rechargeable SNM therapy are maintained and to fully assess the cost-savings associated with rechargeable SNM therapy.…”
Section: Discussionmentioning
confidence: 58%
“…Additional baseline subject characteristics, as well as the efficacy and safety outcomes of this study, were reported previously. 7 …”
Section: Subject Overviewmentioning
confidence: 99%